2021
DOI: 10.5114/aoms/143052
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Fe nanoparticles using Alhagi sparsifolia extract for the treatment of colorectal carcinoma in the in vitro condition: A pre-clinical trial study

Abstract: IntroductionThe preparation and formulation of new chemotherapeutic supplements and drugs with remarkable effects for the treatment of cancer are in the priority of both developing and developed countries. Recently, iron nanoparticles have been used as modern chemotherapeutic drugs for the treatment of several cancers such as leukemia, lung cancer, breast cancer, prostate cancer, etc. In the present study, iron nanoparticles were green-synthesized using the aqueous extract of Alhagi sparsifolia leaf aqueous ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A huge number of proofs showed that ROS was firmly identified with coronary illness, carcinogenesis, atherosclerosis, and different infections related to aging. Nowadays, manufactured cancer prevention agents, generally show undesirable secondary effects [28][29][30][31][32].…”
Section: Antioxidant Properties Of Agnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…A huge number of proofs showed that ROS was firmly identified with coronary illness, carcinogenesis, atherosclerosis, and different infections related to aging. Nowadays, manufactured cancer prevention agents, generally show undesirable secondary effects [28][29][30][31][32].…”
Section: Antioxidant Properties Of Agnpsmentioning
confidence: 99%
“…The progressive development of nanotechnology has been viewed as for regarding disease as well as to the large assortment of utilizations, particularly for medicine conveyance, symptomatic and imaging instances. There are numerous sorts' kinds of nanostructures accessible while picking the right transporters is a crucial matter [31,[41][42][43][44]. Interesting physicochemical properties of AgNPs gives them the simplicity of entry into the cells and enables them to effectively communicate with biomolecules inside the cells or on the cell surfaces [41][42][43][44][45].…”
Section: Anti-breast Adenocarcinoma Activities Analysis Of Agnpsmentioning
confidence: 99%